Wastewater treatment plants: The missing link in global One-Health surveillance and management of antibiotic resistance - Abdolmajid Gholizadeh; Mehdi Khiadani; Maryam Foroughi; Hadi Alizade Siuki; Hadi Mehrfar (Elsevier, 2023)
Introduction: As a global public health crisis, antibiotic resistance (AR) should be monitored and managed under the One-Health concept according to the World Health Organization (WHO), considering the interconnection between humans, animals, and the environment. But this approach often remains focused on human health and rarely on the environment and its compartments, especially wastewater as the main AR receptor. Wastewater treatment plants (WWTPs) not only are not designed for reliving AR but also provide appropriate conditions for enhancing AR through different mechanisms. Methods: By reviewing the research-based statistics on the inclusion of WWTPs in the One-Health/AR program crisis, this paper highlights the importance of paying attention to these hotspots, at first. Also, the importance and technical roadmap for the application of WWTPs in both surveillance and management of AR were provided. The current position of these facilities was also evaluated using strengths, weaknesses, opportunities, and threats (SWOT) analysis. In the end, the concluding knowledge gaps and research needs for future investigations were presented. Results: Despite the fact that wastewater matrices are the hotspot for AR dissemination, WWTPs appear under-represented in One-Health/AR literature. So, of the 414434 articles retrieved for One-Health only 1.5% (n = 6321) focused on AR and about 0.04% (n = 158) on WWTPs. The potential of WWTPs inclusion in AR surveillance has been confirmed by several studies, however, when it comes to its inclusion for management of AR, more evidence should be presented, which confirmed by SWOT results. Discussion: As such, WWTPs simultaneously provide opportunities for AR surveillance as it is assumed that this medium can reflect the reality of the corresponding society, and for managing unexpected crises which could impact the public. Nonetheless, there are still numerous considerations to change WWTPs role from Achilles' heel to Ajax' shield, including strengthening the research-based knowledge and conducting both surveillance and management strategies of AR under One-Health concept (One-Health/AR) in a clear straightforward framework.